Characteristics of speech and swallowing in persons with multiple sclerosis - Silva Banović; Osman Sinanović; Mirsad Muftić (Acta Clinica Croatica)
Inflammation, axonal loss and demyelinating plaques in the brain, which are the background of multiple sclerosis, very often cause changes in speech or dysarthria, in a range from mild to so severe that they impair comprehension of speech by the interlocutor. As a consequence of multiple sclerosis, dysphagia can also occur. The aim of this paper is to present the speech and swallowing difficulties that result from multiple sclerosis, and the importance of assessing the speech and swallowing in people with multiple sclerosis. Th is article is descriptive and provides a comprehensive overview of the literature dealing with this topic. Speech difficulties impede daily functioning and are often the first sign that other people notice. Swallowing difficulties not only complicate daily life but, if not given sufficient attention, are a possible life-threatening consequence of multiple sclerosis. Assessment of speech and swallowing difficulties should be part of the clinical assessment in each person with multiple sclerosis. As multiple sclerosis progresses, so do speech and swallowing difficulties, and it is of utmost importance to provide appropriate treatment that can alleviate these difficulties. Speech-language pathologists should be part of a team making the diagnosis and providing treatment for a person with multiple sclerosis.